Peningkatan Kapasitas Ekonomi Perempuan Koperasi Jeumpa Puteh melalui Pelatihan Perhitungan Harga Pokok Produksi (HPP) - Dewi Maya Sari; Mislinawati Mislinawati; Maliya Syabriyana; Adinda Zahra Apsari; Nabila Syakira; Dara Angreka Soufyan; Abrar Amri (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
The training on the calculation of the cost of goods sold (COGS) at Koperasi Jeumpa Puteh aimed to enhance the economic capacity of its members, particularly women, in managing their micro-businesses. The activity provided basic understanding of COGS, simple financial management, and product marketing techniques. The program also included training in producing antiseptic soap from used cooking oil waste, adopting a circular economy concept to reduce waste and increase product competitiveness. The training results showed an improvement in the members' understanding of COGS, allowing them to calculate production costs and set more accurate selling prices. Furthermore, the members also gained skills in financial management and digital product marketing. This program has had a positive impact on women's empowerment, improving family welfare, and supporting the sustainability of micro-enterprises at the community level.